Nursing and healthcare research at a glance - Glasper, Edward Alan; Rees, Colin (Wiley, 2017)
Nursing and Healthcare Research at a Glance is perfect for nursing and healthcare students, as well as newly qualified practitioners and anyone looking for a refresher or introduction to research. Nursing and Healthcare Research at a Glance is perfect for nursing and healthcare students, as well as newly qualified practitioners and anyone looking for a refresher or introduction to research. Covering a broad range of topics gathered under key sections, this essential book combines informative diagrams and images to provide memorable information for students on one page, and accessible, clearly written text on the facing page. It includes information on a range of quantitative and qualitative research methods, the process of gaining ethical permission, conducting research with special groups including children, and successfully conducting reviews of the literature. Key features include: Clear and informative full colour illustrations throughout An emphasis on need-to-know research information for busy students and healthcare staff A wide range of research methods, currently used in modern healthcare research An impressive line-up of specialist and well-known experts in the field of health and nursing research This book provides quick access to the principles and reality of research and its implementation within the education and practice environment. It is essential reading for anyone in health service education and service settings with limited time who need to draw on research evidence.- Resumé vydavatel
Keywords: ošetřovatelský výzkum; zdravotnický výzkum; nursing research; health care research; učebnice; elektronické knihy; textbooks; electronic books